The influence of liquidity, profitability and solvency on share prices in banking sector companies listed on the IDX in 2019-2021 - Denny Denny; Abdullah Rakhman (Business and Entrepreneurship Department, Kwik Kian Gie School of Business and Information Technology, Jakarta, 2025)
The company's stock price is an indicator of the company's success in assessing its good or bad performance. If the stock price in the market increases, the company successfully manages its business activities well. The theory contained in this study consists of banks, stocks, stock prices, liquidity, profitability, and solvency. This study also has a framework that will formulate research hypotheses. The research object used is banking sector companies listed on the Indonesia Stock Exchange in 2019-2021. The data used is secondary data with sample selection using a non-probability sampling technique with a judgment sampling approach. Hypothesis testing was carried out using descriptive statistical analysis, a regression coefficient convenience test to test data pooling, a classical assumption test, and multiple linear regression analysis with the help of IBM SPSS Statistics 25 software. The results of this study indicate that liquidity has no significant effect on stock prices, profitability has a positive and significant impact on stock prices, and solvency has no significant effect on stock prices. The conclusions of this study are (1) liquidity has no significant effect on stock prices, (2) profitability has a positive and significant effect on stock prices, and (3) solvency has no significant effect on stock prices.